Identifying and measuring economic discrimination - Sergio Pinheiro Firpo (IZA World of Labor, 2017)
Differences in wages between men and women, white and black workers, or any two distinct groups are a controversial feature of the labor market, raising concern about discrimination by employers. Decomposition methods shed light on those differences by separating them into: (i) composition effects, which are explained by differences in the distribution of observable variables, e.g. education level; and (ii) structural effects, which are explained by differences in the returns to observable and unobservable variables. Often, a significant structural effect, such as different returns to education, can be indicative of discrimination.
Keywords: C01; J00; 330; decomposition methods; Oaxaca-Blinder Decomposition; quantile decomposition; wage gap